A Mini Review on Carbon Black Production as Rubber Reinforcement in Tyre Application - Muzakkir Mohammad Zaino; Najaa Mustaffa; Abdull Hafidz Hassan; Ana Najwa Mustapa; Mohamad Hafiz Mamat; Syed Shatir A. Syed-Hassan; Syarifah Nor Faizah Syed Abdul Rahman; Alyaa Amalina Mohd Azli; Khaled Hamdan (Chemical Engineering Transactions)
This review was conducted to assess and provide insights into various methods of carbon black production for use as rubber reinforcement in tyre applications. Journal screening was conducted using the Web of Science database to identify relevant publications and information on carbon black in tyre applications. The analysis covers the number of yearly publications, the countries involved in co-authorship, and keyword co-occurrence related to this topic. This review includes the topic of carbon black production and highlights a literature study on different grades of carbon black and their characteristics used in tyres, such as particle size and surface area. An alternative method for producing carbon black derived from spent tyres is described in this review, focusing on a cyclical process of utilizing and manufacturing carbon black from spent tyres as a potential source of feedstock. This review aims to provide insights into the utilization of various carbon blacks with different properties as rubber reinforcement. The recovery of carbon black from spent tyres could offer a sustainable alternative for its production and utilization.